2006
DOI: 10.1002/art.22138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hormone therapy on risk of hip and knee joint replacement in the women's health initiative

Abstract: Objective. To determine the effect of hormone therapy on arthroplasty rates.Methods. We examined data from the Women's Health Initiative placebo-controlled, double-blind, randomized trials. Community-dwelling women ages 50-79 years were enrolled at 40 US clinics. Women with prior arthroplasty were excluded, yielding a sample size of 26,321 subjects. Women who had had hysterectomies (n ‫؍‬ 10,272) were randomly assigned to receive 0.625 mg/day conjugated equine estrogens (n ‫؍‬ 5,076), or placebo (n ‫؍‬ 5,196),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 37 publications
2
83
1
8
Order By: Relevance
“…While some studies have not shown a significant protective effect of estrogen and incident radiographic knee osteoarthritis, [13] others have found more evidence for a protective effect of estrogen. [14] In the Women's Health Initiative, a randomized double-blind, placebo-controlled trial of estrogen replacement, estrogen supplementation was found to be associated with a slightly significant decreased rate of either hip or knee arthroplasty, (HR = 0.84, 95% CI: 0.7-1.00), but the hazard ratios were insignificant in individual analysis of hip and knee arthroplasty. While these results are of interest, the association of estrogen and incident knee and hip osteoarthritis is still not clearly defined.…”
Section: Ethnicitymentioning
confidence: 96%
“…While some studies have not shown a significant protective effect of estrogen and incident radiographic knee osteoarthritis, [13] others have found more evidence for a protective effect of estrogen. [14] In the Women's Health Initiative, a randomized double-blind, placebo-controlled trial of estrogen replacement, estrogen supplementation was found to be associated with a slightly significant decreased rate of either hip or knee arthroplasty, (HR = 0.84, 95% CI: 0.7-1.00), but the hazard ratios were insignificant in individual analysis of hip and knee arthroplasty. While these results are of interest, the association of estrogen and incident knee and hip osteoarthritis is still not clearly defined.…”
Section: Ethnicitymentioning
confidence: 96%
“…U novije vrijeme postoji sve više dokaza da estrogen ima uticaj na aktivnost zglobnih struktura preko složenih molekularnih puteva koji djeluju na više nivoa [12]. Utvrđeno je da je kod žena koje su uzimale supstitucionu estrogensku terapiju bila manja vjerovatnoća ugradnje vještačkog zgloba kuka ili koljena [13,14]. Bez obzira na brojne studije, postojanje povezanosti hormonske supstitucione terapije i artroze, i dalje je nejasno i zahtijeva dalje istraživanje.…”
Section: Uvodunclassified
“…Duži životni vijek kod žena i posljedično starenje zglobova, takođe potvrđuju prethodnu tvrdnju o značajnijem uticaju ženskog pola na artroze u drugoj polovini života [10,[12][13][14].…”
Section: Diskusijaunclassified
“…einer Östrogen-plusProgestin-Therapie und dem relativen Risiko für eine Arthroplastik [10]. Im Vergleich zur Placebogruppe beobachteten die Forscher bei den Frauen im Östro-gen-mono-Arm ein um 16% verringertes Risiko für eine Arthroplastik (Hazard Ratio, HR, 0,84; 95%-Konfidenzintervall, KI, 0,70-1,00; p<0,05).…”
Section: Introductionunclassified